Biological Ingredient Analysis of Traditional Herbal Patent Medicine Fuke Desheng Wan Using the Shotgun Metabarcoding Approach - Xie, Hongbo; Zhao, Qing; Shi, Mengmeng; Kong, Weijun; Mu, Weishan; Li, Baoli; Zhao, Jingyi; Zhao, Chunying; Jia, Jing; Liu, Jinxin; Shi, Linchun (Frontiers in Pharmacology, 2021)
With the widespread use of traditional medicine around the world, the safety and efficacy of traditional herbal patent medicine have become an increasing concern to the public. However, it is difficult to supervise the authenticity of herbal materials in mixed herbal products according to the current quality standards, especially for traditional herbal patent medicine, with a distinct variance in the dosage of herbal materials. This study utilized the shotgun metabarcoding approach to analyze the biological ingredients of Fuke Desheng Wan (FKDSW), which is an effective traditional herbal product for the treatment of dysmenorrhea. Six herbal materials were collected, and a lab-made FKDSW sample was produced to establish a method for the authentication assessment of biological ingredients in traditional herbal patent medicine based on shotgun metabarcoding. Furthermore, four commercial FKDSW samples were collected to verify the practicality of the shotgun metabarcoding approach. Then, a total of 52.16 Gb raw data for 174 million paired-end reads was generated using the Illumina NovaSeq sequencing platform. Meanwhile, 228, 23, and 14 operational taxonomic units were obtained for the ITS2, matK, and rbcL regions, respectively, after bioinformatic analysis. Moreover, no differences were evident between the assembly sequences obtained via shotgun metabarcoding and their corresponding reference sequences of the same species obtained via Sanger sequencing, except for part of the ITS2 and matK assembly sequences of Paeonia lactiflora, Saussurea costus and Bupleurum chinense with 1-6 different bases. The identification results showed that all six prescribed ingredients were successfully detected and that the non-authentic ingredient of Bupleuri Radix (Chaihu, Bupleurum chinense or Bupleurum scorzonerifolium) was found in all the commercial samples, namely Bupleurum falcatum L. Here, 25 weed species representing 16 genera of ten families were detected. Moreover, 26 fungal genera belonging to 17 families were found in both lab-made and commercial FKDSW samples. This study demonstrated that the shotgun metabarcoding approach could overcome the biased PCR amplification and authenticate the biological ingredients of traditional herbal patent medicine with a distinct variance in the dosage of the herbal materials. Therefore, this provides an appropriate evaluation method for improving the safety and efficacy of traditional herbal patent medicine.